Interspecies care, knowledge and ownership : children’s equestrian cultures in Sweden and Finland - Schuurman Nora; Dirke Karin; Redmalm David; Holmberg Tora (Routledge, 2025)
Riding became a widespread leisure activity for children in Sweden and Finland during the post-war decades through the emergence of riding schools. Drawing on books and comics published in Sweden and Finland from the 1960s to the present, together with interviews and observations at contemporary Swedish riding schools, we approach this development with a geographical, historical and sociological focus. We ask how children’s equestrian cultures were formed within the spaces of horse yards, especially riding schools, and how caring well was understood and negotiated through different types of knowledge and the idea and practice of horse ownership. As we show in the analysis, despite the increase of written knowledge about horses and their care, situated and relational knowledges based on interspecies interaction prevailed in children’s equestrian cultural spheres in which children had a chance to interact with animals and care for them outside the everyday spaces of family and school. In these cultures of interspecies care, ideas of horse ownership carried expectations of continuity where the child–horse relationship was secured and could develop. The entry to these spatial cultures was through rites of passage characterised by embodied interaction and hands-on care, where children learned to care for animals well.